Resonant Raman profiles and micro-photoluminescence of atomically thin layers of molybdenum disulfide - Scheuschner, Nils; Ochedowski, Oliver; Schleberger, Marika; Maultzsch, Janina (physica status solidi (b), 2012)
Schematic crystal structure of molybdenum disulfide. (a) Top view (slightly tilted). (b) Side view. (C) 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: excitons; molybdenum disulfide; photoluminescence; Raman